REKAYASA DIGITAL SISTEM EKONOMI DALAM PENGEMBANGAN EKONOMI SIRKULAR BERBASIS EKONOMI SYARIAH DI KABUPATEN LOMBOK TIMUR - irfan azim; Abdul Khalik; Agus Salihin; Nuraenun Nuraenun (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2026)
The governance of conventional communal waste banks is frequently characterized by managerial inefficiencies and a heavy reliance on manual record-keeping, which fosters information asymmetry. From the perspective of Islamic economics, such conditions manifest as gharar (informational uncertainty), potentially undermining amanah (trust) and ‘adl (fairness in valuation), while simultaneously neglecting the circularity of organic materials—thereby contravening the principle of Hifzh al-Bi’ah (environmental preservation). This study aims to engineer, develop, and evaluate a digital platform ecosystem for waste bank management (SiRKAH) that inherently integrates circular governance with the principles of Maqashid Sharia. Employing the Design Science Research Methodology (DSRM), the system artifact was validated by a multidisciplinary expert panel using the Content Validity Index (CVI) and its efficacy was assessed through field-based operational comparisons (pre- versus post-implementation). The expert validation results confirm a highly robust architectural validity, with an S-CVI score of 0.939. Operationally, the implementation of a digital ijab-qabul protocol (dual authentication) and an immutable ledger has demonstrated significant efficacy disruption: reducing transaction duration by up to 94.2%, completely eliminating (100%) recording errors and balance disputes, and increasing user participation rates by 46.4%. This study contributes to the Green Information Systems (Green IS) literature through the conceptualization of a “Gharar-Free System Architecture,” demonstrating that the fusion of digital technological engineering with religio-communal ethical values constitutes a robust instrument for restoring public trust and accelerating the adoption of a circular economy.